2019
DOI: 10.1128/aac.01801-18
|View full text |Cite
|
Sign up to set email alerts
|

ARGONAUT-I: Activity of Cefiderocol (S-649266), a Siderophore Cephalosporin, against Gram-Negative Bacteria, Including Carbapenem-Resistant Nonfermenters and Enterobacteriaceae with Defined Extended-Spectrum β-Lactamases and Carbapenemases

Abstract: The activity of the siderophore cephalosporin cefiderocol is targeted against carbapenem-resistant Gram-negative bacteria. In this study, the activity of cefiderocol against characterized carbapenem-resistant Acinetobacter baumannii complex, Stenotrophomonas maltophilia, Pseudomonas aeruginosa, and Enterobacteriaceae strains was determined by microdilution in iron-depleted Mueller-Hinton broth. The MIC 90 s against A. baumannii, S. maltophilia, and P. aeruginosa were 1, 0.25, and 0.5 mg/ liter, respectively. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
69
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(80 citation statements)
references
References 26 publications
6
69
0
3
Order By: Relevance
“…Overall, cefiderocol MICs ranged from B 0.002 to 128 lg/mL for all Enterobacterales, compared to 0.008-8 lg/mL for a subset of carbapenem-resistant Enterobacterales from a compilation of worldwide isolates. In surveillance studies, cefiderocol demonstrated more potent in vitro activity against carbapenem-resistant Enterobacterales, A. baumannii and P. aeruginosa, compared to meropenem, CAZ/AVI and TOL/ TAZ [10]. Cefiderocol inhibited [ 98% of CAZ/ AVI and TOL/TAZ non-susceptible Enterobacterales and all CAZ/AVI and TOL/TAZ non-susceptible P. aeruginosa isolates at MICs B 4 lg/ mL, the provisional susceptibility breakpoint from the Clinical and Laboratory Standards Institute (CLSI) [12].…”
Section: In Vitro Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, cefiderocol MICs ranged from B 0.002 to 128 lg/mL for all Enterobacterales, compared to 0.008-8 lg/mL for a subset of carbapenem-resistant Enterobacterales from a compilation of worldwide isolates. In surveillance studies, cefiderocol demonstrated more potent in vitro activity against carbapenem-resistant Enterobacterales, A. baumannii and P. aeruginosa, compared to meropenem, CAZ/AVI and TOL/ TAZ [10]. Cefiderocol inhibited [ 98% of CAZ/ AVI and TOL/TAZ non-susceptible Enterobacterales and all CAZ/AVI and TOL/TAZ non-susceptible P. aeruginosa isolates at MICs B 4 lg/ mL, the provisional susceptibility breakpoint from the Clinical and Laboratory Standards Institute (CLSI) [12].…”
Section: In Vitro Activitymentioning
confidence: 99%
“…A catechol 2-chloro-3,4-dihydroxybenzoic acid moiety on the 3-position of the R2 side chain functions as the siderophore mimic, by chelating extracellular iron and by facilitating enhanced uptake into bacterial periplasmic space via iron transporter channels in the outer membrane. Additionally, a pyrridoline ring bound to the catechol moiety confers zwitterionic properties, similar to those of cefepime, that enhance water solubility of the molecule [9,10]. Once within the periplasmic space, cefiderocol dissociates from the iron and binds to penicillin-binding proteins (PBP), primarily PBP3, to inhibit peptidoglycan synthesis.…”
Section: Chemistry and Mechanism Of Actionmentioning
confidence: 99%
“…In Enterobacterales, variations in iron transport channel expression, which varies by species and within species, may cause a wide distribution of MICs 63 . Compared with ceftazidime-avibactam, cefiderocol has similar in vitro microbiological activity against Enterobacterales and P. aeruginosa, but it is more active against Acinetobacter, Stenotrophomonas and Burkholderia species.…”
Section: New Stand-alone β-Lactam Antibioticsmentioning
confidence: 99%
“…MIC 90 values are about eight doubling dilutions higher in KPC2 producing Enterobacterales than in wild type strains. Due to the very low MICs in wild type strains, the reduction of activity may still keep cefiderocol MICs for many strains below the clinical breakpoint 63 . Similarly, the reduced susceptibility of ESBL producing, carbapenemase producing or AmpC producing strains may not translate into immediate clinical resistance 63 but may be problem atic in critically ill patients with altered pharmacokinetic profiles.…”
Section: New Stand-alone β-Lactam Antibioticsmentioning
confidence: 99%
See 1 more Smart Citation